Pengembangan Sistem Komunikasi Data Dan Jaringan Komputer Dengan Penerapan Wireless Distribution System (WDS) Di SMK Negeri 1 Pringgabaya - M Nuzuluddin (Infotek: Jurnal Informatika dan Teknologi, 2021)
At Present, many schools have used wireless networks that are used to support wired networks. Cable network is used as an amplifier of access point to make internet access for users. The problems of networking using these cables can be a major constraint to inaccessible places that can reduce the flexibility of usage. The solution for this problem is to develop and implement Wireless Distribution System (WDS) on the access point. WDS is a system to develop wireless internet network without having to use cable as backbone for access point but to take advantage of wireless network path from access point. The parameters used in the WDS system are the parameters of jitter, througput, delay and packet loss. WDS performance can be analyzed so that will be known comparison of access point performance results with cable backbone.Keywords: AP (Access Point), WDS,  Wireless Network